2008
DOI: 10.1080/20786204.2008.10873781
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement cycles that reduced waiting times at Tshwane District Hospital Emergency Department

Abstract: Background: Tshwane District Hospital (TDH) is a level-one hospital, delivering services in the centre of Pretoria since February 2006. It is unique in location, being only 100 meters away from the tertiary hospital, Pretoria Academic Hospital (PAH). In South Africa, public sector emergency units are under enormous pressure with large patient numbers, understaffing and poor resources. TDH Emergency Department (ED) is a typical example. An average of 3 900 patients per month visited this ED in 2006. Recurrent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Most studies ( n = 30, 35.3%) that addressed empowerment-enhancing practices considered one empowerment-related practice combined with other practices. Eleven studies researched empowerment-enhancing practices (e.g., team work, supervision) combined with motivation-enhancing practices (e.g., compensation, scheduling) [ 70 , 78 , 99 , 105 , 110 , 115 , 117 , 127 , 136 , 140 , 163 ]. These studies mostly reported improvement on employee outcomes (e.g., satisfaction, retention, performance).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( n = 30, 35.3%) that addressed empowerment-enhancing practices considered one empowerment-related practice combined with other practices. Eleven studies researched empowerment-enhancing practices (e.g., team work, supervision) combined with motivation-enhancing practices (e.g., compensation, scheduling) [ 70 , 78 , 99 , 105 , 110 , 115 , 117 , 127 , 136 , 140 , 163 ]. These studies mostly reported improvement on employee outcomes (e.g., satisfaction, retention, performance).…”
Section: Resultsmentioning
confidence: 99%
“…Primary health care (PHC) centers or clinics vary in terms of resources and infrastructure. A commonly cited problem within the South African public health sector is that of duration of waiting times [ 12 , 13 ]. A study in a South African district hospital showed the average waiting time for stable patients (from arrival of the patient until the start of the consultation by the medical practitioner) was 545 min (~9 h) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A commonly cited problem within the South African public health sector is that of duration of waiting times [ 12 , 13 ]. A study in a South African district hospital showed the average waiting time for stable patients (from arrival of the patient until the start of the consultation by the medical practitioner) was 545 min (~9 h) [ 13 ]. Sitting for hours in a clinic waiting room may pose health risks, particularly when the temperatures and relative humidity (RH) of such waiting rooms are elevated.…”
Section: Introductionmentioning
confidence: 99%
“…3 The average time to treatment of 59 minutes in this study is within the national Department of Health target of 120 minutes. 20 It could only be established that 16.2% of cases were seen outside the recommended time but this data item should be interpreted with caution due to the large percentage of undocumented times. This is worrying, in the context of escalating medical litigation in the public sector.…”
Section: Discussionmentioning
confidence: 96%